Analisis Wacana Kritis Politik Oligarki dalam Podcast Bocor Alus Politik "Bedah Kasus Pertamina dan Jaringan Politik Riza Chalid" YouTube Tempo.co - Lailatul Magfiroh; Heidy Arviani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines oligarchic political discourse in Tempo.co’s Bocor Alus Politik podcast episode “Pertamina and Riza Chalid’s Political Network.” It investigates how political–economic power relations are represented in media narratives when discussing Indonesia’s energy governance, particularly regarding fuel imports, policy “conditioning,” and elite networks. The research employs a descriptive qualitative design and Teun A. van Dijk’s Critical Discourse Analysis framework, focusing on the dimensions of text, social cognition, and social context. The findings show that the podcast constructs oligarchy as a mode of power operating beyond formal state institutions through interconnected political and business actors that mutually reinforce protection and access. Riza Chalid is framed not merely as a businessman but as an informal political actor perceived to influence national energy policy and the distribution of rents. Evaluative lexical choices such as “Gasoline Godfather,” “old modus,” and the metaphor “out of the tiger’s mouth into the crocodile’s jaws” function to sharpen criticism that the issue is not reducible to individual wrongdoing, but rooted in structural continuity and the reproduction of networks. These results align with Jeffrey A. Winters’s concept of oligarchy as income defense, in which political power is used to secure wealth accumulation and protection by a narrow elite. Practically, the podcast as a digital platform operates as a space of counter-discourse, expanding public understanding of the nexus between media, power, and energy politics.